PERAN PARLEMEN DALAM PERLINDUNGAN ANAK - Kurniawan, Teguh (Jurnal Aspirasi, 2015)
This study aims to explain the conditions of the protection of children, the role of government and the role of the Parliament within the protection of children. The data obtained through library needed. The data has been categorized, classified, and reduced then be concluded in accordance with the objectives of the study. Results of this study concluded that the government has provided protection for children through legal instruments and ratification of various laws on children. However, the government’s role in the protection seen as less effective, therefore, was born then several institutions aimed at protecting children, the National Commission for Child Protection (National Commission on Children) and the Indonesian Child Protection Commission (LPAI). Parliament as a legislative institution, also plays a role in the protection of children, especially to establish laws, monitoring of government policies, and the budget allocated for the realization of child protection in Indonesia.